Les petits exploitants agricoles et l’État brésilien sur la frontière avec la Guyane française - Martins-Faure Laurença (Confins)
Agents of transformation of the territory, both the State and smallholders, compete for recognition of their actions in the border area between Brazil and French Guiana. By the creation and implementation of strategies of appropriation of the border area, each player becomes an agent of transformation of the territory. The Brazilian government is the main actor of this transformation, either by the imposition of rules to protect the border, through the dissemination of economic development programs and, more recently, sustainable development. Smallholders, often migrants from other parts of Brazil, part of the official policy, respecting the rules imposed by questioning their viability, or integrating these policies in their strategies of economic agents. This social construction is the node structure exchanges between actors. Highlighting these exchanges can target more specifically the measures in support of productive activities agricultural area international border.